PENGARUH KUALITAS PRODUK, PERSEPSI HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI HOURS COFFEE AND MORE JAKARTA - Hadiwijaya, Tasya (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2022)
This study aims to assess the impact of product quality, price perception, and service quality on customer satisfaction at Hours Coffee and More Jakarta and other companies. This study uses a survey-based quantitative research design using a purposive sample of 100 respondents. This study uses primary data, or data collected directly from respondents, which includes their perceptions of aspects of product quality, price perceptions, and service quality. According to research findings, consumer satisfaction at Hours Coffee and More Jakarta is not significantly influenced by product quality, but price perceptions have a positive and significant impact. At Hours Coffee and More Jakarta, service standards also have a significant effect on customer satisfaction. Finally, the combined findings show that consumer satisfaction at Hours Coffee and More Jakarta is significantly influenced by product quality, price perception, and service quality.